2006
DOI: 10.1007/s10681-006-9224-2
|View full text |Cite
|
Sign up to set email alerts
|

QTL mapping of fiber quality in an elite hybrid derived-RIL population of upland cotton

Abstract: Xiangzamian 2 (XZM2) was the most widely cultivated cotton hybrid planted as F 1 hybrids and as selfed F 2 seeds in China before the release of transgenic Bt hybrids. By crossing two parents of XZM2, Gossypium hirsutum cv. Zhongmiansuo12 (ZMS12) and G. hirsutum acc. 8891, and through subsequent selfings, we obtained F 8 and F 9 populations of 180 recombinant inbred lines (RILs). A RIL population was cultivated in two cotton-growing regions in China for 2 years. The purpose of the present research was to detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
35
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(50 citation statements)
references
References 25 publications
13
35
0
2
Order By: Relevance
“…Here we found many common characteristics of QTLs related to fiber quality traits as described in the previous reports involving interspecific maps [3,10,23,[33][34][35][36][37][38] and intraspecific maps [12,15,26,30,[39][40][41][42][43][44][45][46], although few common markers were used in the present research and the previous studies, and the maps covered different region parts of cotton genome, making it difficult to compare the common QTLs, some QTLs were detected and mapped on the same chromosomes and affect common traits. These include seven QTLs for fiber length located in the same chromosomal regions as reported earlier [10,26,34,41,42], two QTLs for fiber uniformity ratio located in the same chromosomal regions [43,46], two QTLs for fiber micronaire [10,43,44], three QTLs for fiber elongation [30,36,42,43,46,47], and 4 QTLs for fiber strength [26,34,36,43,44,46,47].…”
Section: Qtls For Cotton Fiber Quality Traitssupporting
confidence: 69%
See 1 more Smart Citation
“…Here we found many common characteristics of QTLs related to fiber quality traits as described in the previous reports involving interspecific maps [3,10,23,[33][34][35][36][37][38] and intraspecific maps [12,15,26,30,[39][40][41][42][43][44][45][46], although few common markers were used in the present research and the previous studies, and the maps covered different region parts of cotton genome, making it difficult to compare the common QTLs, some QTLs were detected and mapped on the same chromosomes and affect common traits. These include seven QTLs for fiber length located in the same chromosomal regions as reported earlier [10,26,34,41,42], two QTLs for fiber uniformity ratio located in the same chromosomal regions [43,46], two QTLs for fiber micronaire [10,43,44], three QTLs for fiber elongation [30,36,42,43,46,47], and 4 QTLs for fiber strength [26,34,36,43,44,46,47].…”
Section: Qtls For Cotton Fiber Quality Traitssupporting
confidence: 69%
“…These include seven QTLs for fiber length located in the same chromosomal regions as reported earlier [10,26,34,41,42], two QTLs for fiber uniformity ratio located in the same chromosomal regions [43,46], two QTLs for fiber micronaire [10,43,44], three QTLs for fiber elongation [30,36,42,43,46,47], and 4 QTLs for fiber strength [26,34,36,43,44,46,47]. For example, the chromosome regions where QTLs were detected for fiber length in our research matched those in an interspecific map developed from an F 2 population [10]; the QTLs may be common QTLs for fiber quality traits.…”
Section: Qtls For Cotton Fiber Quality Traitsmentioning
confidence: 70%
“…Transgressive segregations exceeded Nazilli-84 in L, and both parents in a, b, ∆a, ∆b and ∆E values. There are transgressive segregations reported in fiber related traits in the literature (Wang et al, 2006;Shen et al, 2007;Qin et al, 2008;Luan et al, 2009;, which were consistent with our current results. It has been also demonstrated that F 2 hybrids can exhibit superior performance for agronomic and fiber traits when compared with their parental lines (Gutiérrez et al, 2002).…”
Section: Discussionsupporting
confidence: 93%
“…This could be due to either limited marker coverage or having no detectable QTL on the linkage groups. However, similar results regarding this issue were reported in previous studies Wang et al, 2006;He et al, 2007;Wu et al, 2009). …”
Section: Discussionsupporting
confidence: 91%
“…Mapping populations are obtained using two contrasting parents for the desired trait. In self-pollinated crops; usually mapping populations include F 2 [56,57]; F 2:3 [58,59], recombinant inbred lines (RILs) [60,61], backcross (BC) [62,63], Backcross inbred lines (BILs) [64], near isogenic lines [65,66], doublehaploids [67,68], chromosome substitution lines (CSILs) [69,70]. F 2 , BC, RILs and doublehaploids have been highly used for linkage mapping studies in cotton.…”
Section: Mapping Populationmentioning
confidence: 99%